Characterization and Prediction of Short-term Outcomes in Memory After Temporal Lobe Resection in Children With Epilepsy. (2nd May 2023) - Kaur, Navkiranjot; Nowacki, Amy S.; Lachhwani, Deepak K.; Berl, Madison M.; Hamberger, Marla J.; Klaas, Patricia; Bingaman, William; Busch, Robyn M.
Abstract : Background and Objectives: The aim of this study was to characterize short-term outcomes in episodic memory, as assessed by the Children's Memory Scale (CMS), after temporal lobe resection in children with epilepsy using empirical methods for assessing cognitive change (i.e., reliable change indices [RCI] and standardized regression-based change scores [SRB]) and develop and internally validate clinically applicable models to predict postoperative memory decline. Methods: This retrospective cohort study included children aged 6–16 years who underwent resective epilepsy surgery that included the temporal lobe (temporal only: "temporal" and multilobar: "temporal plus") and who completed preoperative and postoperative neuropsychological assessments including the CMS. Change scores on the CMS delayed memory subtests (Faces, Stories, and Word Pairs) were classified as decline, no change, or improvement using epilepsy-specific RCI and SRB. Logistic regression models for predicting postoperative memory decline were developed and internally validated with bootstrapping. Results: Of the 126 children included, most of them demonstrated either no significant change (54%–69%) or improvement (8%–14%) in memory performance using RCI on individual measures at a median of 7 months after surgery. A subset of children (23%–33%) showed postoperative declines. Change distributions obtained using RCI and SRB were not statistically significantly different from each other. Preoperative memory test score, surgery side, surgery extent, and preoperative full-scale IQ were predictors of memory decline. Prediction models for memory decline included subsets of these variables with bias-corrected concordance statistics ranging from 0.70 to 0.75. The models were well calibrated although slightly overestimated the probability of verbal memory decline in high-risk patients. Discussion: This study used empiric methodology to characterize memory outcome in children after temporal lobe resection. Provided online calculator and nomograms may be used by clinicians to estimate the risk of postoperative memory decline for individual patients before surgery.